Evolution of a multi‐step phosphorelay signal transduction system in Ensifer: recruitment of the sigma factor RpoN and a novel enhancer‐binding protein triggers acid‐activated gene expression. Issue 5 (9th January 2017) - Tian, Rui; Heiden, Stephan; Osman, Wan A. M.; Ardley, Julie K.; James, Euan K.; Gollagher, Margaret M.; Tiwari, Ravi; Seshadri, Rekha; Kyrpides, Nikos C.; Reeve, Wayne G.
Summary: Most Ensifer strains are comparatively acid sensitive, compromising their persistence in low pH soils. In the acid‐tolerant strain Ensifer medicae WSM419, the acid‐activated expression of lpiA is essential for enhancing survival in lethal acidic conditions. Here we characterise a multi‐step phosphorelay signal transduction pathway consisting of TcsA, TcrA, FsrR, RpoN and its cognate enhancer‐binding protein EbpA, which is required for the induction of lpiA and the downstream acvB gene. The fsrR, tcrA, tcsA and rpoN genes were constitutively expressed, whereas lpiA and acvB were strongly acid‐induced. RACE mapping revealed that lpiA / acvB were co‐transcribed as an operon from an RpoN promoter. In most Ensifer species, lpiA/acvB is located on the chromosome and the sequence upstream of lpiA lacks an RpoN‐binding site. Nearly all Ensifer meliloti strains completely lack ebpA, tcrA, tcsA and fsrR regulatory loci. In contrast, E . medicae strains have lpiA/acvB and ebpA/tcrA / tcsA / fsrR co‐located on the pSymA megaplasmid, with lpiA/acvB expression coupled to an RpoN promoter. Here we provide a model for the expression of lpiA/acvB in E. medicae . This unique acid‐activated regulatory system provides insights into an evolutionary process which may assist the adaptation of E. medicae to acidic environmental niches. Abstract : A multistep phosphorelay signal transduction system regulates the acid‐activated expression of lpiA/acvB in Ensifer medicae WSM419. Regulation involves a two component sensor/regulator (TcsA/TcrA), a fused sensor‐regulator (FsrR), the recruitment of the sigma factor RpoN and a novel cognate enhancer‐binding protein EbpA. This system is found in the species E. medicae and is absent from the species Ensifer meliloti except in the case of Mlalz‐1, for which there is evidence of horizontal gene transfer.